SPACE-TEMPORAL EVOLUTION OF THE USE AND OCCUPATION OF THE LAND ALONG THE PARAGUAY RIVER'S CORRIDOR, UPPER PANTANAL - BRAZIL - Santos Leandro, Gustavo Roberto dos [UNESP]; Nascimento, Flavio Rodrigues do; Souza, Celia Alves de (Univ Federal Goias, Inst Estudos Socio-ambientais, 2019)
This research was carried out in Caceres - Mato Grosso, on the Paraguay River, upper Pantanal - Brazil, and its objective was to analyze the changes of coverage with the advance of land use and occupation along the period from 1980 to 2013. Thus, images LANDSAT were georeferenced, classified and processed, while the thematic class, quantified and edited. In addition to the cabinet procedures, fieldwork was carried out, which allowed the identification of the main ways of using the banks and channels of the river system. The research showed that the main economic activity developed is cattle ranching with gradual values over the years - the same more than doubled from 1984 to 2003. The results evidenced important transformations in the landscape with significant suppressions of the vegetal cover, that is, in the period analyzed, in more than 50% of the area there was some kind of transformation - deforestation or conversion of uses (pasture areas for urban expansion). Concerning to the edges' channel, engineering repairs were the main alternatives adopted to contain the erosive processes, especially in the urban perimeter and in concave sections, parallel to BR-070.
Keywords: Fluvial system; Landscape changes; Use and occupation; Pleasant and denudational and aggradational environments